Micromechanical properties of Dy3+ ion-doped (LuxY1-x)3Al5O12 (x = 0, 1/3, 1/2) single crystals by indentation and scratch tests. Issue 3 (1st February 2023) - Liu, Ming; Hou, Dongyang; Wang, Yan; Lakshminarayana, G.
Abstract: Three kinds of Dy 3+ ion-doped (Lu x Y1- x )3 Al5 O12 ( x  = 0, 1/3, 1/2) single crystals fabricated by the Czochralski method with 4 at.% Dy 3+ ion doping were investigated by indentation and scratch techniques under Vickers, Knoop, Berkovich, and spherical indenters to understand the influence of Lu ion on micromechanical properties and fracture behavior of Y3 Al5 O12 (i.e. YAG for x  = 0) single crystals. The largest (or smallest) values of hardness, elastic modulus, and fracture toughness were found for x  = 1/3 (or 1/2). The indentation size effect was explained by four different models with the Hays-Kendall approach being the most suitable one to determine the true hardness. Fracture toughness values of YAG crystals obtained by the Vickers hardness method agreed with those obtained by scratching with a spherical indenter based on linear elastic fracture mechanics.